2023
DOI: 10.1111/aji.13764
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of hydrogen sulfide production and pregnancy rate in an experimental model: Association with preterm delivery

Abstract: ProblemPro‐inflammatory phenomena drive preterm delivery (PTD). Hydrogen sulfide is a gasotransmitter with anti‐inflammatory properties produced through the activity of the enzyme cystathionine‐γ‐lyase (CSE), and its impact was studied in models of normal delivery and PTD in mice.Method of studyFemale CSE+/+ and CSE−/− mice were mated with male CSE+/+ mice; mating was done with drinking water unsupplemented and supplemented with cysteine. The pregnancy rate was monitored. PTD was induced by the intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Recent research focused on the fertility of CSE-KO mice showed that CSE-KO leads to a reduced number of successful pregnancies and a higher pro-inflammatory status of fetuses. This suggests that CBS is not the sole key enzyme in H 2 S production in the context of female reproduction ( 70 ).…”
Section: Detection Of H 2 S-producing Enzymes and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research focused on the fertility of CSE-KO mice showed that CSE-KO leads to a reduced number of successful pregnancies and a higher pro-inflammatory status of fetuses. This suggests that CBS is not the sole key enzyme in H 2 S production in the context of female reproduction ( 70 ).…”
Section: Detection Of H 2 S-producing Enzymes and ...mentioning
confidence: 99%
“…Besides its tocolytic effects, H 2 S may also impact uterine immune response and placental vessel remodeling through the modulation of the uterine natural killer (uNK) cells ( 121–123 ). H 2 S signaling is also essential for maintaining early pregnancy, and its deficiency can lead to reduced litter size due to early embryo loss or placental inflammation ( 70 , 124 ). H2S may further facilitate the physiological implantation of the embryo by regulating ion transport activity in the endometrial epithelium and supporting DNA synthesis ( 125–127 ).…”
Section: Detection Of H 2 S-producing Enzymes and ...mentioning
confidence: 99%